Income and yield effects of climate-smart agriculture (CSA) adoption in flood prone areas of Bangladesh: Farm level evidence - Asma Akter; Xianhui Geng; Gershom Endelani Mwalupaso; Hua Lu; Fazlul Hoque; Michael Kiraru Ndungu; Qasir Abbas (Climate Risk Management, 2022)
Understanding the effects of climate change adaptation measures by smallholder farm households in flood-prone areas remains underdeveloped. Particularly, little is known whether adoption of climate-smart agriculture (CSA) augments crop yield and income. Therefore, we investigate the impact of CSA adoption on yield and income in Bangladesh, one of the countries of the world most vulnerable to climate change and disaster prone. To achieve this, based on primary data from a sample of 600 smallholder farms, the endogenous switching regression (ESR) is applied while controlling for endogeneity issues and selection bias of CSA adoption. For robustness check, propensity score matching (PSM) is applied. Consistent results from both models are found indicating that CSA adoption has yield and income effects on smallholder farms. Interestingly, if non-adopting households are soil salinity conscious and adopt CSA, their yield would increase by 7.55%. In addition, non-adopting households would significantly have tremendous income gains on account of CSA adoption. Results demonstrate that policy support measures for CSA adoption in flood-prone areas can have important implications for food security and poverty eradication through crop yield boosts and income augmentation in line with the purview of the sustainable development goals (SDGs).